Noise exposure files for a polysomnographic study of ground-borne noise from railway tunnels and sleep - Pilot study - Ögren, Mikael (University of Gothenburg, 2018)
In residential areas around railway tunnels, there is no direct airborne noise from the railways, but residents may be exposed to ground borne noise. Nocturnal airborne railway noise has been shown to be potentially disruptive to sleep, but there is only limited previous research on the effects of ground borne railway noise. This study present laboratory studies investigating how ground borne railway noise at levels occurring in the field impacts on sleep. Data on sound pressure level, duration and frequency content of ground borne noise from railways were collected from the scientific literature, from measurement reports and by renewed measurements at a few locations in Stockholm, Sweden.

The audio files were created to simulate a ground borne noise from a tunnel close to the dwelling. Both files are dominated by low frequencies, but one has more of the lowest frequencies (denoted “LF” in the filename).

Purpose:

The audio files were used as exposure in a sleep study focused on the effect on ground borne noise from railway tunnels.

Noise exposure files for the pilot study, the files marked RCG are simulate freight train passages, and files marked X55 are passenger trains. A,B and C denotes the different spectra.

I bostadsområden nära järnvägstunnlar hörs inga luftburna ljud från järnvägen, men invånarna kan utsättas för stomljud. Luftburna ljud nattetid har visat sig ha potentiellt störande effekter på sömnen, men sedan tidigare finns begränsad mängd forskning om effekterna av stomljud från järnvägen. I studien har laboratorieundersökningar gjors för att ta reda på vad markburet järnvägsbuller har för påverkan på sömnen.

Ljudfilerna i studien skapades för att simulera stomljud från en tågtunnel i nära anslutning till bostaden. Båda filerna domineras av låga frekvenser, men den fil där de låga frekvenserna framträder starkast har beteckningen "LF" i filnamnet.

Syfte:

Ljudfilerna användes som exponering i en sömnstudie med inriktning på effekterna av stomljud från järnvägstunnlar.

Ljudfilerna i pilotstudien som är märkta med "RCG" simulerar godståg som passerar förbi och filerna som är märkta med "X55" är passagerartåg. "A", "B" och "C" betecknar olika ljudspektrum.
Ljudfiler för en sömnstudie av stomljud från järnvägstunnlar - Pilotstudie
Keywords: trains; tåg; sleep; sömn; rail traffic; järnvägstrafik; Polysomnography; Sömnövervakning; railway tunnels; järnvägstunnlar; Other Civil Engineering; Annan samhällsbyggnadsteknik; Health; Hälsa